Review of Heath Lees. 2007. Mallarmé and Wagner: Music and Poetic Language. Aldershot, UK, and Burlington, VT: Ashgate Publishing - Code, David J. (Current Musicology, 2008)
Heath Lees’s book Mallarmé and Wagner: Music and Poetic Language offers a relatively straightforward revisionist claim: that Mallarmé’s familiarity with (and agonistic response to) the challenge of Wagnerian music drama cannot be solely attributed- as it sometimes has been- to a Damascene “conversion” contemporaneous with the “second wave” of French ‘wagnérisme’ in the mid-1880’s. The true roots of this central strand of the poet’s though, Lees argues, extend much deeper than this, even as far back as his formative years as a Lycéen during the late 1850s. Reappraised in this light, Mallarmé’s “quest to re-appropriate music on behalf of poetry” must be seen as a crucial determinant not only of his few, explicit late responses to Wagner, but most of his works starting from his first publications in the 1860’s.